ASSESSMENT OF THE FEASIBILITY OF INVESTMENT PROJECTS FOR THEENTERPRISE MODIFICATION ON EXAMPLE OF «UMAN BREAD TRADE» LLC - HUK, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of the feasibility of investment projects for the enterprise «Uman Bread Trade» LLC, which specializes in the production of bakery products. Given the high level of competition, economic instability, and technological challenges, the need for a systematic approach to investment management is emphasized. The main focus is on the adaptation of universal valuation methods, such as NPV (net present value), IRR (internal rate of return), PP (payback period), PI (profitability index) to the specifics of medium-sized enterprises. The study analyzes the key aspects of investment project evaluation, including the financial condition of the enterprise, forecasting the economic effect of pr ojects, as well as taking into account risks and financial constraints. An economic and mathematical model for evaluating the effectiveness of investments is proposed, consisting of three stages: formation of an information base, calculation of key indicators, and comprehensive project evaluation using expert methods. Particular attention is paid to the structure of the investment potential of the enterprise, which includes financial, market and organizational components. The key advantages of «Uman Bread Trade» LLC are highlighted, including the quality and freshness of products, the availability of its own sales network, as well as stable demand for products. The conclusions of the article emphasize the importance of implementing innovative projects to ensure the    sustainable development of the enterprise. Further research should focus on developing methods for risk assessment, finding effective sources of financing, and optimizing management decisions in the context of economic instability. The results may be useful for other enterprises in the industry.
Keywords: investment projects; enterprise modernization; automatization; performance evaluation; NPV (net present value); risk management